Pain practice in Nepal thirty years ago: A practitioner's Quest - Swar, Bal Bahadur (Journal of Society of Anesthesiologists of Nepal, 2018)
The article describes the initial days of the authors pain practice in Nepal. Journal of Society of Anesthesiologists of Nepal Vol. 4, No. 2, 2017, Page: 49-53